Macamides from wild ‘Maca’, Lepidium meyenii Walpers (Brassicaceae) - Chain, Fernando Ezequiel (2014)
The non-polar extract of the tubers of Lepidium meyenii Walpers yielded two benzylated alkamides (macamides), N-(3,4-dimethoxybenzyl)-hexadecanamide (1) and N-benzyltetracosanamide (2). The structure elucidation of the compounds was based on 1D and 2D NMR spectroscopic analyses, including 1H–1H COSY, 1H–13C HSQC, 1H–13C HMBC, 1H–15N HSQC and HMBC experiments.